Association of genetic variation in the tachykinin receptor 3 locus with hot flashes and night sweats in the Women's Health Initiative Study. Issue 3 (March 2017) - Crandall, Carolyn J.; Manson, JoAnn E.; Hohensee, Chancellor; Horvath, Steve; Wactawski-Wende, Jean; LeBlanc, Erin S.; Vitolins, Mara Z.; Nassir, Rami; Sinsheimer, Janet S.
Abstract: Objective: Vasomotor symptoms (VMS, ie, hot flashes or night sweats) are reported by many, but not all, women. The extent to which VMS are genetically determined is unknown. We evaluated the relationship of genetic variation and VMS. Methods: In this observational study, we accessed data from three genome-wide association studies (GWAS) (SNP Health Association Resource cohort [SHARe], WHI Memory Study cohort [WHIMS+], and Genome-Wide Association Studies of Treatment Response in Randomized Clinical Trials [GARNET] studies, total n = 17, 695) of European American, African American, and Hispanic American postmenopausal women aged 50 to 79 years at baseline in the Women's Health Initiative Study. We examined genetic variation in relation to VMS (yes/no) in each study and using trans-ethnic inverse variance fixed-effects meta-analysis. A total of 11, 078, 977 single-nucleotide polymorphisms (SNPs) met the quality criteria. Results: After adjustment for covariates and population structure, three SNPs (on chromosomes 3 and 11) were associated with VMS at the genome-wide threshold of 5 × 10 −8 in the African American SHARe GWAS, but were not associated in the other cohorts. In the meta-analysis, 14 SNPs, all located on chromosome 4 in the tachykinin receptor 3 ( TACR3 ) locus, however, had P < 5 × 10 −8 . These SNPs' effect sizes were similar across studies/participants' ancestry (odds ratio ∼1.5). Conclusions: Genetic variation in TACR3 may contribute to the risk of VMS. To our knowledge, this is the first GWAS to examine SNPs associated with VMS. These results support the biological hypothesis of a role for TACR3 in VMS, which was previously hypothesized from animal and human studies. Further study of these variants may lead to new insights into the biological pathways involved in VMS, which are poorly understood. Abstract : Supplemental Digital Content is available in the text